Nano Sweeper / Muhammad Amir Hamzah Mohd Yusof - Mohd Yusof, Muhammad Amir Hamzah (2020)
Recently, to find a cleaning tools that can help people for stay clean and healthy is quite difficult. Many of manufacturer companies are selling products that never care about the people healthy and risk toward that particular. The Nano sweeper concept actually taken from nature. This nano-sweeper promised you to have better environment that free rubbish and small particle such as dust with high recommended nature element used. The hairs of sweeper are made up of natural element such as charcoal. To improve the absorption of dust and effectiveness during cleaning process this sweeper has been modified with Nano element. Nano element act as ions absorption that contains of negatively and positively charges, this allow the attachment and attraction of other particles onto the sweeper hairs. Transmissions of negatively and positively ions. Remove bacteria or viruses. The ions attach themselves to the surface of microbe and viruses it will transform into highly oxidative OH radicals which is the hydrogen will drain out and combines with the OH radicals and turn into water, H2O molecules. Effective dust, pollens and other particles traps. This sweeper design with two layers of hair to make it more efficient during cleaning process by trapping the dust or other small particles prevent them from dispersal onto the air. Materials use for making this sweeper made up from the good and high qualities materials such as carbon, alloy and natural element such as charcoal. In this product we use carbon and alloy because it light in weight and also have strong which is suitable for long period use. In addition, it also can reduce the risk of joint pain, reduce tiredness, and muscle cramp.